2019
DOI: 10.1080/00318884.2019.1640533
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds as nutraceuticals for health and nutrition

Abstract: Throughout human history, seaweeds have been used as food, folk remedies, dyes, and mineral-rich fertilisers. Seaweeds as nutraceuticals or functional foods with dietary benefits beyond their fundamental macronutrient content, are now a major research and industrial development concept. The occurrence of dietary and lifestyle-related diseases, notably type 2 diabetes, obesity, cancer, and metabolic syndrome has become a health epidemic in developed countries. Global epidemiological studies have shown that coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 129 publications
1
104
0
7
Order By: Relevance
“…Minerals are fundamental for the good performance of the human body, and Palmaria palmata (Rhodophyta) could be a good iron resource because it contains 800 mg/kg dw. In the European Union, the recommended iron uptake dosage is 14 mg/day [14,15].…”
Section: Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minerals are fundamental for the good performance of the human body, and Palmaria palmata (Rhodophyta) could be a good iron resource because it contains 800 mg/kg dw. In the European Union, the recommended iron uptake dosage is 14 mg/day [14,15].…”
Section: Mineralsmentioning
confidence: 99%
“…Lipids have widespread applications, such as food and dietary supplements and pharmaceutical [6,21]. However, total lipid content is present, on average, in seaweeds in concentrations between 0.60% and 4.15% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Undaria pinnatifida is an edible brown alga belonging to the family Alariaceae. According to a clinical trial conducted by Shannon and Abu-ghannam [63] found that the daily supplementation of Undaria pinnatifida balanced the blood glucose levels in patients with type 2 diabetes mellitus. In addition, Sharifuddin et al [64] found that the consumption of rice-based breakfast supplemented by Undaria pinnatifida reduced the postprandial blood glucose concentration in healthy volunteers.…”
mentioning
confidence: 99%
“…Bu analiz ile C. protothecoides biyoaktif değere sahip olan ve faydalı çoklu doymamış yağ asitleri bakımından zengin olduğu görülmüştür. Alg kaynaklı yağ asitleri adenozin trifosfat enerji transferini engeller ve bakteriyel enoil-açil taşıyıcı protein redüktaz gibi enzimleri inhibe eder ve daha sonra hücre lizizi ve peroksidasyonu ve oto-oksidasyon bozunma ürünleri meydana gelir [12]. Çalişkan Eleren ve Öneri [22], sürdürülebilir ve çevre dostu biyoyakıt hammaddesi üretimi için yaptıkları çalışmada C. protothecoides'in lipit içeriğini %50.50 olarak belirlemiştirler.…”
Section: Protothecoides'in Gaz Kromatografi (Gc) Analiziunclassified
“…Mikroalglerin yüksek antioksidan etkisi, α-tokoferol, βkaroten, glutatyon, askorbik asit, flavonoidler, hidrokinonlar, fikosiyaninler, prolin, fenolik bileşikler ve poliaminler gibi antioksidan bileşiklerinden kaynaklanmaktadır [11]. C. protothecoides'in içerdiği; lutein, astaksantin ve zeaksantin gibi biyoaktif bileşikler antioksidan aktiviteye sahiptir, aynı zamanda bakterilere ve fungal mikroorganizmalara karşı da etkilidirler [12]. Son yıllarda mikroalglerle ilgili pek çok çalışma olmasına ragmen gıda koruyucusu olarak antimikrobiyal etkilerinin araştırıldığı çalışmalar sınırlı kalmıştır.…”
unclassified